Monitoring ssDNA Binding to the DnaB Helicase from Helicobacter pylori by Solid‐State NMR Spectroscopy. Issue 45 (6th October 2016) - Wiegand, Thomas; Cadalbert, Riccardo; Gardiennet, Carole; Timmins, Joanna; Terradot, Laurent; Böckmann, Anja; Meier, Beat H.
Abstract: DnaB helicases are bacterial, ATP‐driven enzymes that unwind double‐stranded DNA during DNA replication. Herein, we study the sequential binding of the "non‐hydrolysable" ATP analogue AMP‐PNP and of single‐stranded (ss) DNA to the dodecameric DnaB helicase from Helicobacter pylori using solid‐state NMR. Phosphorus cross‐polarization experiments monitor the binding of AMP‐PNP and DNA to the helicase. 13 C chemical‐shift perturbations (CSPs) are used to detect conformational changes in the protein upon binding. The helicase switches upon AMP‐PNP addition into a conformation apt for ssDNA binding, and AMP‐PNP is hydrolyzed and released upon binding of ssDNA. Our study sheds light on the conformational changes which are triggered by the interaction with AMP‐PNP and are needed for ssDNA binding of H. pylori DnaB in vitro. They also demonstrate the level of detail solid‐state NMR can provide for the characterization of protein–DNA interactions and the interplay with ATP or its analogues. Abstract : 31 P and 13 C solid‐state NMR spectroscopy reveal binding and conformational activation of the dodecameric DnaB helicase by the ATP‐analogue AMP‐PNP, and its subsequent release when DNA in turn binds to the protein. While the N‐terminal domain remains unaffected by these events, the C‐terminal domain switches conformation upon nucleotide binding and release.